ADHERENCE DECREASES WITH HIGHER NUMBER OF MEDICATIONS IN CONTROLLED HYPERTENSIVE PATIENTS, CONTROLLED RESISTANT PATIENTS HAVE LOWER ADHERENCE THAN CONTROLLED NON-RESISTANT PATIENTS. (April 2021) - Siddiqui, Mohammed; Gupta, Pankaj; Tomazewski, Maceij; Patel, Prashanth; Oparil, Suzanne; Calhoun, David
Abstract : Objective: Controlled hypertension in treated hypertensive patients is defined as controlled blood pressure (BP) in clinic (automated office BP [AOBP] < 130/80 mmHg) and out-of-clinic by 24-hr ambulatory blood pressure monitoring (ABPM < 125/75 mmHg). Uncontrolled resistant hypertension (RHTN) is defined as uncontrolled blood pressure (BP) on 3 or more medications, including a diuretic; BP controlled on 4 or more medications is defined as controlled RHTN. Controlled non-RHTN is BP controlled on 3 or less medications. Antihypertensive medication adherence is known to decrease with increase in number of antihypertensive medications, as well as medication adherence is lower in patients with uncontrolled RHTN. Unknown is the relative medication adherence in patients with controlled hypertension with number of antihypertensive medications and medication adherence in controlled RHTN versus controlled non-RHTN. Design and method: In this prospective evaluation patients were recruited from the Hypertension Clinic after having controlled BP readings at 3 or more clinic visits. All the patients were evaluated by in-clinic AOBP with use of the BpTRU device, out-of-clinic 24-hr ABPM monitoring and 24-hr urine collection to determine antihypertensive medication adherence by high-performance liquid chromatography-tandem mass spectrometry. After excluding patients with masked uncontrolled hypertension, 82 patients were controlled by AOBP and 24-hr ABPM. Of these, 40 patients had controlled RHTN and 42 patients had controlled non-RHTN. Results: Higher number of prescribed antihypertensive medications was associated with lower levels of medication adherence in patients with controlled hypertension. In addition, patients with controlled RHTN (72.7%) had significantly lower medication adherence than controlled non-RHTN (90.9%). Figure. No caption available. Conclusions: Similar to uncontrolled hypertension, patients with controlled hypertension have less medication adherence with use of higher numbers of antihypertensive medications. In addition, similar to uncontrolled RHTN, patients with controlled RHTN have lower medication adherence than patients with controlled non-RHTN.